2015
DOI: 10.1088/1054-660x/25/3/035202
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of fidelity of molecular DNA computing using laser spectroscopy

Abstract: This work is devoted to application of laser Raman spectroscopy to improve the fidelity of molecular computing by DNA strands. The developed method provides determination of concentrations of specific nitrogenous bases not lower than 0.03 g l −1 and the accuracy of determining the total concentration of DNA in solutions 0.02-0.04 g l −1 by the Raman spectra of DNA solutions. The method allows us to control the temperature of DNA solutions in the process of molecular computing with an accuracy better than 0.2 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…In addition, for a DNA concentration range of 0-9 g l −1 [30], the calibration dependence of the intensity of the nitrogenous base markers on its concentration could be approximated really well by a straight line. However, according to the literature, for a concrete problem the maximal concentration of DNA can vary within rather wide limits-from 3.32 g l −1 [33] up to 32.5 g l −1 [34].…”
Section: Problem Of Reliability Of Dna Computingmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, for a DNA concentration range of 0-9 g l −1 [30], the calibration dependence of the intensity of the nitrogenous base markers on its concentration could be approximated really well by a straight line. However, according to the literature, for a concrete problem the maximal concentration of DNA can vary within rather wide limits-from 3.32 g l −1 [33] up to 32.5 g l −1 [34].…”
Section: Problem Of Reliability Of Dna Computingmentioning
confidence: 82%
“…The authors of this publication have demonstrated that Raman spectroscopy allowed us to determine (in non-contact real-time mode) both the total concentration of DNA molecules in the solution and the concentration of individual nitrogenous bases in their single-component solutions, using the calibration dependencies of Raman marker bands of nitrogenous bases (figure 1) on their concentration in the range of 0 to 9 g l −1 [30,31]. Also it was shown that the use of laser Raman spectroscopy for monitoring biochemical reactions provided for the detection and control of the processes of renaturation and denaturation of DNA strands, determination of the state of the strands, and the control of possible mutations in DNA molecules [32].…”
Section: Problem Of Reliability Of Dna Computingmentioning
confidence: 99%
“…To minimize the effect of elastic scattering and extract useful Raman signal of water in the spectral region of 50–300 cm −1 , we used the so‐called R‐representation method proposed by Brooker et al The measured Raman intensity I ( ω ) can be expressed by I()ω=Cω0ωi4Siωi()1ehωickT where C is a constant, ω 0 is the absolute wavenumber (in wavenumber units) of the excitation laser line, ω i is the Raman shift, S i is the intrinsic molar scattering activity at ω i for a Raman process, h is the Plank constant, k is the Boltzman constant, c is the speed of light, and T is the absolute temperature. To eliminate the dependence on temperature and wavenumber, a reduced Raman spectrum R ( ω ) is defined as normalR()ω=ωi()1ehωickT()ω0ωi4normalI()ω …”
Section: Resultsmentioning
confidence: 99%
“…where C is a constant, ω 0 is the absolute wavenumber (in wavenumber units) of the excitation laser line, ω i is the Raman shift, S i is the intrinsic molar scattering activity at ω i for a Raman process, h is the Plank constant, k is the Boltzman constant, c is the speed of light, and T is the absolute temperature. To eliminate the dependence on temperature and wavenumber, a reduced Raman spectrum R(ω) is defined as [56,57] R ω ð Þ ¼…”
Section: Segmental Drsmentioning
confidence: 99%
“…Then, the dependencies of the intensity of each of the specified markers of A, T, C, and G on their concentration in water in the range from 0 to 5 g/L with the concentration increment of 0.5 g/L were obtained. As in the other studies of the authors of this article, it turned out that these dependencies are well-approximated by straight lines (Figures and S1–S3). Moreover, the dependences of the intensities of the markers on the concentration of the corresponding NBs in water with/without the addition of NaOH coincided in the relevant concentration ranges of DNA NBs.…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%